2020
DOI: 10.1007/s00267-020-01347-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of DDT in Agricultural Soils under Organic Farming in Poland and the Risk of Crop Contamination

Abstract: The analysis of 142 agricultural soil samples collected in organic farms across Poland with the intent to evaluate the level of DDT contamination resulted in more than 80% of the soils containing DDT. The ΣDDT (sum of all metabolites and isomers) concentration ranged between 0.005 and 0.383 mg/kg ΣDDT, with an average value of 0.064 mg/kg ΣDDT. However, the majority of plant samples collected from the crops growing on the sampled soils did not contain detectable DDT residues. The high DDT pollution levels dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
(66 reference statements)
3
7
1
1
Order By: Relevance
“…As shown in Table 5 and Figure 5 (summations), we found significant differences in the concentrations of p,p’-DDE, p,p-DDD, and dieldrin, although in the opposite directions to those theorized by other authors [ 72 , 73 ]. Our results indicated that the concentration of organochlorines in farms devoted to mixed vegetable cultivation was much higher than that in vineyards, which would present levels very much in line with those reported recently in studies around the world [ 65 , 66 , 67 , 68 , 69 ]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Table 5 and Figure 5 (summations), we found significant differences in the concentrations of p,p’-DDE, p,p-DDD, and dieldrin, although in the opposite directions to those theorized by other authors [ 72 , 73 ]. Our results indicated that the concentration of organochlorines in farms devoted to mixed vegetable cultivation was much higher than that in vineyards, which would present levels very much in line with those reported recently in studies around the world [ 65 , 66 , 67 , 68 , 69 ]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Resultssupporting
confidence: 91%
“…This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place. much in line with those reported recently in studies around the world [65][66][67][68][69]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Application To Agricultural Soil Samplessupporting
confidence: 87%
See 1 more Smart Citation
“…The plants were separated from soil and each plant fraction (root, aboveground and sometimes fruits) together with remaining soil were analysed for DDT residues. DDT and its metabolites were determined as described elsewhere [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic halogenic pollutants such as 1,1,1-Trichloro-2,2-bis (4-chlorophenyl) ethane (DDT) and its metabolite products (e.g., 1,1-dichloro-2,2-bis (4-chlorophenyl) ethane (DDD), and 1,1-dichloro-2,2-bis (4-chlorophenyl) ethylene (DDE)) have accumulated in soils and pose significant health and environmental concerns [ 1 , 2 ]. In particular DDT-polluted agricultural sites are of great human health concern due to the environmental persistence of DDT and its metabolite products becoming long-term sources of exposure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%